THE NINTH-GRADE STUDENTS' PERCEPTION ON TEACHING ENGLISH THROUGH JIGSAW METHOD IN EFL AT SMPN 1 TARAKAN - Noor Mutiara,; Daniel, Daniel; Arifin, Arifin (Jurnal Cakrawala Ilmiah, 2022)
The purpose of teaching and learning English is to be proficient in communication, and this is something that is emphasized in both the curriculum and methodology for English as a foreign language. This study aims to determine students' perceptions of the Jigsaw method, after studying from home for two years, in English subject. The subjects in this study were ninth grade students of SMPN 1 Tarakan who had studied English using the Jigsaw method. The data in this study are the results of filling a questionnaire with scale likert. The findings in this study indicate that students prefer English lessons when using the Jigsaw method compared to learning individually. Teachers are expected to make an improvement in the process of learning English in class by using learning methods or innovations or learning creations so that students can learn easily and have fun.